Pengaruh Substitusi Pasir Limbah Tailing Emas Sebagai Agregat Halus terhadap Sifat Mekanik Beton Normal - Riko Ardiansyah; Hariyadi Hariyadi; Nurul Hidayati (Universitas Batanghari Jambi, 2026)
The increasing demand for natural sand as fine aggregate in concrete mixtures encourages the utilization of more environmentally friendly alternative materials, one of which is gold mining tailings waste sand. This study aims to analyze the effect of substituting gold mining tailings waste sand as a partial replacement for fine aggregate on the fresh concrete characteristics and mechanical properties of normal concrete. The research was conducted experimentally using four mixture variations, namely normal concrete, BTL 10%, BTL 20%, and BTL 30%. The concrete mix design referred to SNI 03-2834-2000, while the specimens were cylindrical with dimensions of 150 mm × 300 mm and tested at the age of 28 days. The parameters tested included slump value, fine aggregate specific gravity, compressive strength, and splitting tensile strength. The results showed that normal concrete had the highest compressive strength of 20.27 MPa, while the 10% tailings variation decreased by 9.22% to 18.40 MPa, the 20% variation decreased by 4.75% to 19.31 MPa, and the 30% variation decreased by 0.09% to 20.25 MPa. In the splitting tensile strength test, normal concrete had a value of 1.72 MPa, while the 10%, 20%, and 30% variations had values of 1.75 MPa, 1.73 MPa, and 1.72 MPa, respectively. These results indicate that the use of gold mining tailings waste sand up to 30% is still capable of producing compressive strength nearly equivalent to normal concrete, while the 10% substitution provided the highest increase in splitting tensile strength of 1.37% compared to normal concrete. This study demonstrates that gold mining tailings waste sand has the potential to be utilized as an environmentally friendly alternative fine aggregate material without significantly reducing the mechanical properties of concrete